6. ve 7. sınıf öğrencilerinin matematiksel sözel, sembolik ve görsel dili anlama ve kullanma becerilerinin incelenmesi - Yıldız, Figen (My University, 2016)
6. ve 7. SINIF ÖĞRENCİLERİNİN MATEMATİKSEL SÖZEL, SEMBOLİK VE GÖRSEL DİLİ ANLAMA VE KULLANMA BECERİLERİNİN İNCELENMESİ Bu araştırmanın amacı 6. ve 7. sınıf öğrencilerinin kesirler konusunda matematiksel dili ve matematiksel dilin alt boyutlarını (sözel, sembolik ve görsel) kullanma ve anlama düzeylerinin belirlenmesidir. Ayrıca matematiksel dili anlama ve kullanma düzeyi ile matematik başarısı arasındaki ilişkiyi tespit etmek ve öğrencilerin matematiksel dili nasıl kullandığını incelemek amaçlanmıştır. Bu çalışmada çoklu araştırma modeli kullanılmıştır. Araştırmanın nicel boyutunda toplanan veriler tarama modeli kullanılarak analiz edilmiştir. Araştırmanın çalışma grubunu İstanbul ili Ümraniye ilçesindeki bir devlet okulunun 35’i altıncı sınıf, 35’i yedinci sınıf olmak üzere 70 öğrenci oluşturmaktadır. Araştırmanın nitel boyutunda doküman analizi ve yarı yapılandırılmış görüşme yapılmıştır. Veriler araştırmacı tarafından geliştirilen “Matematik Başarı Testi” ve “Matematiksel Dili Anlama ve Kullanma Beceri Formu” ölçme araçları ile toplanmış ve bir istatistik paket SPSS) ile analiz edilmiştir. Araştırma sonucunda öğrencilerin %50’sinin matematiksel dili kısmen doğru kullanabilmekte olduğu, matematiksel dil puanları ile matematiksel başarı puanları arasında yüksek korelasyon (r=0,70 ) olduğu tespit edilmiştir. Matematiksel dili doğru kullanabilen öğrencilerin matematiksel başarılarının da yüksek olduğu sonucuna ulaşılmıştır. Matematiksel dilin sınıf düzeyine göre farklılaşması incelendiğinde yedinci sınıf öğrencilerinin matematiksel dil puanının altıncı sınıf öğrencilerininkinden anlamlı düzeyde farklı olduğu sonucuna ulaşılmıştır(p=0,026, p<0,05). Dilin alt boyutları incelendiğinde öğrencilerin en yüksek dil puanının görsel dil puanı olduğu, daha sonra sembolik dil puanı olduğu en düşük ise sözel dil puanı olduğu sonucuna ulaşılmıştır. Matematik Öğretimi, Matematiksel dil, Sembolik dil, Görsel dil, Sözel dil, Kesirler, Matematik Başarısı

AN INVESTIGATION OF 6th AND 7th GRADE STUDENTS' MATHEMATICAL VERBAL, SYMBOLIC AND VISUAL LANGUAGE COMPREHENSION AND USE ABILITIES The aim of this study is to determine 6th and 7th grade students' comprehension and use levels of mathematical language and its sub-dimensions (verbal, symbolic and visual) about fractions. Moreover, it is aimed to determine relationship between level of the use and comprehension of mathematical language and mathematical success and to examine how students use mathematical language. In this study, the multiple research model was used. On the quantitative basis, the data of the research was analyzed by using the scanning model. The students’ mathematical success, verbal language marks, symbolic language marks, visual language marks and mathematical language marks were calculated and then the relationships between these variables were examined. The participants of the research were gathered from 70 students, 35 of them were at the 6th grade and 35 of them were at the 7th grade, in Ümraniye province of İstanbul. The data was collected via “Mathematical Success Test” and “The Comprehension and Usage Skills of Mathematical Language Form” developed by the researcher and analyzed through a statistical package programme (SPSS). In order to establish whether there was a significant difference between the variables, two sample t-test independent of parametric tests and two sample t-test dependent on parametric tests were used. Moreover, the Pearson Moments Correlation factor was calculated in order to determine the level of the relationship between the variables. On the qualitative dimension of the this study, documentary analysis and half structural interview were applied. On the documentary analysis, the answers given to the linguistic scale were examined one by one and these answers were grouped into specific titles. These half-structured interviews were held with 16 students; 9 of them were at the 6th grade and 7 of them were at the 7th grade. The interviews were audio recorded with the permission of the students. As a result of research, we established that 50% of students use the mathematical language partially correctly and that there was a high correlation (r=0,70) between the mathematical languag and success marks. We may infer that the students using the mathematical language correctly will be succesful in Maths. When we analyzed the differention of mathematical language according to the class levels, we concluded that there was a significant difference between the mathematical language marks of seventh grade students and that of sixth grade students (p=0,026, p<0,05). When we examined the subscales of language, we concluded that the highest language mark was visual language mark, and second one was symbolic language mark, and the lowest one was verbal language mark. Key Words: Teaching Maths, Mathematical language, Symbolic language, Visual language, Verbal language, Fractions, Mathematics Success.
Keywords: Eğitim ve öğretim; Matematik; Türkiye